The mind-body relationship in psychotherapy: grounded cognition as an explanatory framework - Leitan, Nuwan D.; Murray, Greg (Frontiers in Psychology, 2014)
As a discipline, psychology is defined by its location in the ambiguous space between mind and body, but theories underpinning the application of psychology in psychotherapy are largely silent on this fundamental metaphysical issue. This is a remarkable state of affairs, given that psychotherapy is typically a real-time meeting between two embodied agents, with the goal of facilitating behavior change in one party. The overarching aim of this paper is to problematize the mind-body relationship in psychotherapy in the service of encouraging advances in theory and practice. The paper briefly explores various psychotherapeutic approaches to help explicate relationships between mind and body from these perspectives. Themes arising from this analysis include a tendency toward dualism (separation of mind and body from the conceptualization of human functioning), exclusivism (elimination of either mind or body from the conceptualization of human functioning), or mind-body monism (conceptualization of mind and body as a single, holistic system). We conclude that the literature, as a whole, does not demonstrate consensus, regarding the relationship between mind and body in psychotherapy. We then introduce a contemporary, holistic, psychological conceptualization of the relationship between mind and body, and argue for its potential utility as an organizing framework for psychotherapeutic theory and practice. The holistic approach we explore, “grounded cognition”, arises from a long philosophical tradition, is influential in current cognitive science, and presents a coherent empirically testable framework integrating subjective and objective perspectives. Finally, we demonstrate how this “grounded cognition” perspective might lead to advances in the theory and practice of psychotherapy.